2019
DOI: 10.11604/pamj.2019.32.71.17698
|View full text |Cite
|
Sign up to set email alerts
|

Severe odontogenic infections: a 5-year review of a major referral hospital in Ghana

Abstract: Introduction Odontogenic infections are fairly common in healthcare settings. However, late presentations such as Ludwig's angina, facial cellulitis, necrotizing cervical fasciitis (NCF), among others could lead to mortality. In view of suggestions that the occurrence of severe, near-fatal odontogenic infections is declining, this study set out to determine the incidence of such severe odontogenic infections over the past 5 years at the Korle-Bu Teaching Hospital, a major referral centre in Ghana.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 11 publications
2
25
1
7
Order By: Relevance
“…The distribution of orofacial infection was higher in the third decade of life, with 55 cases (20.8%) and near equal disruption between the sexes. The same trend was noted in other developing countries [ 49 ].…”
Section: Discussionsupporting
confidence: 86%
“…The distribution of orofacial infection was higher in the third decade of life, with 55 cases (20.8%) and near equal disruption between the sexes. The same trend was noted in other developing countries [ 49 ].…”
Section: Discussionsupporting
confidence: 86%
“…However, there was 7% mortality from the infections. This rate is higher than rates reported in a similar Ghanaian study by Blankson et al, which reported a 5.8% fatality rate (23). Late presentation was a common factor in both the Kenyan and Ghanaian fatalities.…”
Section: Orofacial Infectionscontrasting
confidence: 62%
“…However, these infections continue to be a very common presentation in our environment [9]. Despite being one of the common conditions seen at our hospital there are no published reports from our centre, however there are few reports from Southern Ghana [10,11]. This study seeks to review our experience with DNSIs at the ENT Unit of the Tamale Teaching Hospital.…”
Section: Introductionmentioning
confidence: 99%